2008
DOI: 10.1213/ane.0b013e3181884bbf
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Pretreatment Reduces Ceramide Production and Attenuates Intestinal Mucosal Apoptosis Induced by Intestinal Ischemia/Reperfusion in Rats

Abstract: The findings indicate that propofol pretreatment attenuates II/R-induced intestinal epithelial apoptosis, which might be attributable to its antioxidant property modulating the ceramide pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 33 publications
1
38
0
2
Order By: Relevance
“…It has recently focused greater attention due to its anti-apoptosis capability and antioxidant property [35][36][37][38]. However, the direct effect of propofol on hypoxic osteoblasts has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently focused greater attention due to its anti-apoptosis capability and antioxidant property [35][36][37][38]. However, the direct effect of propofol on hypoxic osteoblasts has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that propofol limits myocardial ischemia/reperfusion injury with an associated reduction in apoptotic cell deaths in rats (13), and it attenuates intestinal ischemia/reperfusion induced intestinal epithelial apoptosis which might be attributable to its antioxidant property modulating the ceramide pathway (14). Moreover, propofol protects hepatic L02 cells from These results suggest that the application of propofol has potential to reduce apoptosis through the JNK pathway and Bim down-regulation.…”
Section: Discussionmentioning
confidence: 74%
“…Prophylactic antiapoptotic treatment can be an effective therapeutic strategy for the prevention of I/R injury [22] . Thiopental is a highly lipid-soluble anesthetic, which has indicated antioxidant effect by inhibiting lipid peroxidation in ischemia/reperfusion injury [17] .…”
Section: Discussionmentioning
confidence: 99%